Contribuições para a produção e consumo responsável na região de Passo Fundo: cadeia de alimentos orgânicos na pandemia - Soares, João Filipe Torres (2021)
Based on SDGs 2, 3, 11 and 12 and the concepts of short value supply chains and fair trade, it is demonstrated that with Passo Fundo's prominent position in the region it is possible to establish an agro ecological and/or organic production network since there is sufficient food demand and that this planning would enhance regional and local resilience, promote public health, actively contribute to diminishing hunger and, above all, improve the region's performance in terms of responsible production and consumption by improving the sharing of values and promoting access to quality food. The objective of this research is to verify how e-commerce and new information technologies can help family producers of agro ecological and organic products in the Passo Fundo’s region to improve their business performance and increase their income. For its elaboration, an extensive bibliography was gathered to characterize the international, national and regional scene about the subject. Two questionnaires were prepared and applied to producers and consumers to identify contact points and cleavages, and qualitative and quantitative indicators were defined to analyse the information collected. In the end, an action demonstrating the intersection of the concepts of agro ecology and organic agriculture with fair trade and short value chains applied to a digital trade scenario was analysed, with the purpose of launching the academic debate on the importance of new information technologies and digital platforms as support for traditional activities. The study was carried out in the city of Passo Fundo and the COREDE Produção’s region, a space that is defined by 21 municipalities. It is hoped that this work will lay the foundations for a discussion on digital support for traditional but emerging sustainable production activities, contributing positively to the identification of factors that prevent Sustainable Development Goal (SDG) 12 from being synergetic, putting at risk the results of the 2030 agenda for its main interactions and finally promoting a rapprochement by raising consumer awareness of the need for a change in consumption habits for the benefit of humankind.